2021
DOI: 10.1523/jneurosci.0031-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

Model-Based Planning Deficits in Compulsivity Are Linked to Faulty Neural Representations of Task Structure

Abstract: Compulsive individuals have deficits in model-based planning, but the mechanisms that drive this have not been established. We examined two candidates—that compulsivity is linked to (1) an impaired model of the task environment and/or (2) an inability to engage cognitive control when making choices. To test this, 192 participants performed a two-step reinforcement learning task with concurrent EEG recordings, and we related the neural and behavioral data to their scores on a self-reported transdiagnostic dimen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 70 publications
2
25
0
Order By: Relevance
“…Thus, we dissociated generalized from obsessive worry using the same approach taken in previous studies ( Doron et al, 2012 ; Stein et al, 2010 ), namely, by including a measure of OCD symptoms as a control covariate. Controlling for OCD symptoms has the additional benefit of accounting for known relations between OCD and poor learning of task structure, reduced MB control, and perseverative tendencies ( Gillan et al, 2016 ; Seow et al, 2021 ; Sharp et al, 2021 ). Secondly, another potentially confounding relationship exists between worry and somatic anxiety ( Sharp et al, 2015 ), likely reflecting a general anxiety factor.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we dissociated generalized from obsessive worry using the same approach taken in previous studies ( Doron et al, 2012 ; Stein et al, 2010 ), namely, by including a measure of OCD symptoms as a control covariate. Controlling for OCD symptoms has the additional benefit of accounting for known relations between OCD and poor learning of task structure, reduced MB control, and perseverative tendencies ( Gillan et al, 2016 ; Seow et al, 2021 ; Sharp et al, 2021 ). Secondly, another potentially confounding relationship exists between worry and somatic anxiety ( Sharp et al, 2015 ), likely reflecting a general anxiety factor.…”
Section: Resultsmentioning
confidence: 99%
“…These probabilities are referred to as state transitions, and participants' estimates of these state transitions can be inferred from the two-step task (Daw et al 2005). Recent applications of this task have revealed that individuals high in compulsive traits misestimate these probabilities, resulting in impaired learning (Seow et al 2021;Sharp et al 2021). Misestimating first-order uncertainty in the consequences of one's own action may then constitute a core aspect of compulsivity, and is thought to underlie checking behaviour in obsessive-compulsive disorder (Fradkin et al 2020).…”
Section: "First-order" Uncertainty: Uncertainty That Cannot Be Reducedmentioning
confidence: 99%
“…Compulsive traits (Seow et al 2021;Sharp et al 2021) OCD (Marzuki et al 2022;Vaghi et al 2017) Adults with ASD (Arthur et al 2021)…”
Section: Actionsmentioning
confidence: 99%
“…Thus, we dissociated generalized from obsessive worry using the same approach taken in previous studies 62,63 , namely, by including a measure of OCD symptoms as a control covariate. Controlling for OCD symptoms has the additional benefit of accounting for known relations between OCD and poor learning of task structure, reduced model-based control, and perseverative tendencies [64][65][66] . Secondly, another potentially confounding relationship exists between worry and somatic anxiety 28 , likely reflecting a general anxiety factor.…”
Section: Empirical Evidence Of Each Computational Strategymentioning
confidence: 99%